2017
DOI: 10.1007/s10561-017-9628-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological incorporation of human acellular dermal matrix used in Achilles tendon repair

Abstract: Human acellular dermal matrices (ADMs) are used successfully in a variety of procedures, including sports medicine related, wound repair, and breast reconstructions, but the mechanism of repair is still not fully understood. An opportunity to explore this mechanism presented itself when a patient experienced a rerupture of the native tendon due to a fall that occurred 2 months after undergoing an Achilles tendon repair using Matracell treated ADM. The ADM was removed and an extensive histology analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…23,30 During the decellularization processes, it is important to preserve intact unique structures and matrix components for tissue development and wound healing. [31][32][33][34][35][36][37] Here, we provide a modified method for the decellularization of porcine sclera by using cells disrupted with a salt solution, the mild detergent Triton X-100, and supernuclease. The results from histological staining, SEM, and TEM confirmed the undamaged architecture and retention of active ingredients in the ECM, suggesting that scleral collagen fibers did not suffer evident disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,30 During the decellularization processes, it is important to preserve intact unique structures and matrix components for tissue development and wound healing. [31][32][33][34][35][36][37] Here, we provide a modified method for the decellularization of porcine sclera by using cells disrupted with a salt solution, the mild detergent Triton X-100, and supernuclease. The results from histological staining, SEM, and TEM confirmed the undamaged architecture and retention of active ingredients in the ECM, suggesting that scleral collagen fibers did not suffer evident disruption.…”
Section: Discussionmentioning
confidence: 99%
“…During the decellularization processes, it is important to preserve intact unique structures and matrix components for tissue development and wound healing 31‐37 . Here, we provide a modified method for the decellularization of porcine sclera by using cells disrupted with a salt solution, the mild detergent Triton X‐100, and supernuclease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the biomechanical properties of grafts may influence wound healing at the wound edges 7 following surgical interventions, with the scaffold’s stiffness being a strong regulator of stem cell differentiation 8 . Human acellular skin is a widely deployable graft material, which has, among others, been used for the treatment of chronic wounds 9 , congenital skin absence 10 , tendon repair 11 or cleft palate repair 5 . This given study is part of the ongoing Human Head Tissues Biomechanics project, which focuses on the mechanical description of human head tissues and their biomechanically adequate surgical replacement.…”
Section: Introductionmentioning
confidence: 99%
“…31 As a genetically engineered endonuclease, benzonase has been used for decellularizing dermis and corneas. 32,33 Benzonase can quickly infiltrate into corneal stroma, efficiently degrade all forms of DNA and RNA without proteolytic activity, and also easily be removed by repeated washing. 34 Supernuclease is a homologous nuclease of benzonase.…”
Section: Introductionmentioning
confidence: 99%